Implementation of Prospective Bride and Groom Courses in North Balantak District, Banggai Regency - Jarudin , Jarudin; Hilal Malarangan; Yamani, Gasim; Hamiyuddin, Hamiyuddin (INTERNATIONAL JOURNAL OF CONTEMPORARY ISLAMIC LAW AND SOCIETY, 2024)
This study aims to evaluate the implementation of prospective bride and groom courses in Balantak Utara District, Banggai Regency, focusing on efforts to improve household quality through pre-marital counseling. The high number of divorce cases and the large number of unregistered marriages, as well as the low public awareness of Islamic teachings and the fulfillment of basic needs, indicate the need for prospective bride and groom courses as a means to improve family conditions in this area. The study used a qualitative approach with data collection techniques through observation, in-depth interviews, and document analysis. The results showed that implementing prospective bride and groom courses in Balantak Utara District consisted of three stages: guidance at the KUA, health guidance at the Community Health Center, and further guidance by education practitioners and counselors. However, the implementation of pre-marital guidance at the KUA was not optimal, with shortcomings in delivering material on harmonious family relationships and preparation for a quality generation. Meanwhile, guidance at the Community Health Center has been implemented quite well regarding reproductive health and healthy lifestyles, but further guidance has not been fully implemented. This study suggests the need to improve facilities and infrastructure as well as competent teaching staff to support the achievement of a harmonious family in Balantak Utara District